Self-Consistent Two-Gap Approach in Studying Multi-Band Superconductivity of NdFeAsO0.65F0.35 - Gupta, Ritu; Maisuradze, Alexander; Zhigadlo, Nikolai D.; Luetkens, Hubertus; Amato, Alex; Khasanov, Rustem (Frontiers in Physics, 2020)
High quality single crystals of NdFeAsO0.65F0.35 (the superconducting transition temperature Tc ≃ 30.6 K) were studied in zero-field (ZF) and transverse-field (TF) muon-spin rotation/relaxation (μSR) experiments. An upturn in muon-spin depolarization rate at T ≲ 3 K was observed in ZF-μSR measurements and it was associated with the onset of ordering of Nd electronic moments. Measurements of the magnetic field penetration depth (λ) were performed in the TF geometry. By applying the external magnetic field Bex parallel to the crystallographic c-axis (Bex||c) and parallel to the ab-plane (Bex||ab), the temperature dependencies of the in-plane component (λab-2) and the combination of the in-plane and the out of plane components (λab,c-2) of the superfluid density were determined, respectively. The out-of-plane superfluid density component (λc-2) was further obtained by combining the results of Bex||c and Bex||ab set of experiments. The temperature dependencies of λab-2, λab,c-2, and λc-2 were analyzed within the framework of a self-consistent two-gap model despite of using the traditional α-model. Interband coupling was taken into account, instead of assuming it to be zero as it stated in the α-model. A relatively small value of the interband coupling constant Λ12 ≃ 0.01 was obtained, thus indicating that the energy bands in NdFeAsO0.65F0.35 are only weakly coupled. In spite of their small magnitude, the coupling between the bands leads to the single value of the superconducting transition temperature Tc. The penetration depth anisotropy γλ = λc/λab was found to increase upon cooling, consistent with most of Fe-based superconductors, and their behavior is attributed to the multi-band nature of superconductivity in NdFeAsO0.65F0.35.